Functional Restoration of BRCA1 Nonsense Mutations by Aminoglycoside-Induced Readthrough - Abreu, Renata B. V.; Gomes, Thiago T.; Nepomuceno, Thales C.; Li, Xueli; Fuchshuber-Moraes, Mateus; De Gregoriis, Giuliana; Suarez-Kurtz, Guilherme; Monteiro, Alvaro N. A.; Carvalho, Marcelo A. (Frontiers in Pharmacology, 2022)
BRCA1 is a major tumor suppressor that functions in the accurate repair of DNA double-strand breaks via homologous recombination (HR). Nonsense mutations in BRCA1 lead to inactive truncated protein products and are associated with high risk of breast and ovarian cancer. These mutations generate premature termination codons (PTCs). Different studies have shown that aminoglycosides can induce PTC suppression by promoting stop codon readthrough and restoring full-length (FL) protein expression. The use of these compounds has been studied in clinical trials for genetic diseases such as cystic fibrosis and Duchenne muscular dystrophy, with encouraging results. Here we show proof-of-concept data demonstrating that the aminoglycoside G418 can induce BRCA1 PTC readthrough and restore FL protein synthesis and function. We first demonstrate that G418 treatment restores BRCA1 FL protein synthesis in HCC1395, a human breast tumor cell line carrying the R1751X mutation. HCC1395 cells treated with G418 also recover HR DNA repair and restore cell cycle checkpoint activation. A set of naturally occurring BRCA1 nonsense variants encoding different PTCs was evaluated in a GFP C-terminal BRCA1 construct model and BRCA1 PTC readthrough levels vary depending on the stop codon context. Because PTC readthrough could generate FL protein carrying pathogenic missense mutations, variants representing the most probable acquired amino acid substitutions in consequence of readthrough were functionally assessed by a validated transcription activation assay. Overall, this is the first study that evaluates the readthrough of PTC variants with clinical relevance in the breast and ovarian cancer-predisposing gene BRCA1.